Trickster : Native American tales : a graphic collection. - Dembicki, Matt (Fulcrum Books, 2010)
This anthology collects over twenty trickster stories, in graphic novel format, from various Native American traditions, including tales about coyotes, rabbits, ravens, and other crafty creatures and their mischievous activities. All cultures have tales of the trickster, a crafty creature or being who uses cunning to get food, steal precious possessions, or simply cause mischief. He disrupts the order of things, often humiliating others and sometimes himself. In Native American traditions, the trickster takes many forms, from coyote or rabbit to raccoon or raven. This graphic anthology of Native American trickster tales brings together Native American folklore and the world of comics. More than twenty Native American tales are adapted into comic form. Each story is written by a different Native American storyteller who worked closely with a selected illustrator, a combination that gives each tale a unique and powerful voice and look. Ranging from serious and dramatic to funny and sometimes downright fiendish, these tales bring tricksters back into popular culture in a very vivid form.